Pembelajaran Tilawah Al-Quran Braille: Pengalaman Pusat Penyelidikan Ibnu Ummi Maktum (Ummi) USIM - Mohd Nur Adzam Rasdi; Noornajihan Ja‘afar; Norakyairee Mohd. Raus; Mahyuddin Hashim; Nur Amalina Azhar; Muhammad Shahril Azrie Zainudin; Zakaria Yahya; Sharipah Zainah Abdul Rahman; Anisah Razali (Universiti Sains Islam Malaysia, 2024)
PAPER PROCEEDINGS THE 7TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2021 “ISLAMIC AND NON-REVEALED KNOWLEDGE IN FACING THE GLOBAL CHALLENGES” 6th – 7th October 2021 / 29 – 30 Safar 1443H Faculty of Quranic and Sunnah Studies Universiti Sains Islam Malaysia